Software for Planning Precise Intraoperative Correction of Rotational Deformity of Extremity. - Gangadharan, Sangeet; Markandaya, Surrendra (Techniques in Orthopaedics, 2018)
Most of the torsional deformities of the limbs correct spontaneously with growth. Corrective derotation osteotomy forms the mainstay of treatment for symptomatic residual deformities. The described techniques for calculation of intraoperative assessment of rotational correction involve approximation of calculations and measures. We have designed a new method of computation with minimal error. For derotation osteotomy of subtrochanteric region of femur, preoperatively, the magnitude of rotational correction of the femur is measured by computed tomography. The cross section of femur at subtrochanteric level resembles closely to a circle or ellipse. Following osteotomy, the major and minor axis are measured. The magnitude of correction will correspond to the arc length of the circle/ellipse. The calculation carried out by numerical integration using Python programming language. Once the arc length is obtained, the osteotomy is fixed with the desired implant. Postoperative computed tomographic scan is performed to assess rotational correction. Unlike previously described techniques, our study provides the closest possible approximation in intraoperative calculation of rotational correction of torsional deformity of any long bone. We believe that this technique would yield more accurate results thus averting possibility second surgery. Further studies are required to validate its accuracy in clinical use.